Recent Advances in the Pathogenesis and Drug Action in Periodic Paralyses and Related Channelopathies - Tricarico, Domenico; Conte Camerino, Diana (Frontiers in Pharmacology, 2011)
The periodic paralysis(PP) are rare autosomal-dominant disorders associated to mutations in the skeletal muscle sodium, calcium and potassium channel genes characterized by muscle fiber depolarization with un-excitability, episodes of weakness with variations in serum potassium concentrations. Recent advances in thyrotoxic-PP(TPP) and hypokalemic-PP(hypoPP) confirm the involvement of the muscle potassium channels in the pathogenesis of the diseases and their role as target of action for drugs of therapeutic interest. The novelty in the gating pore currents theory help to explain the disease symptoms, and open the possibility to more specifically target the disease. It is now known that the fiber depolarization in the hypoPP is due to an unbalance between the novel identified depolarizing gating pore currents(Igp) carried by protons or Na+ ions flowing through aberrant alternative pathways of the mutant subunits and repolarizing inwardly rectifying potassium channel(Kir) currents which also includes the ATP-sensitive subtype. Abnormal activation of the Igp or deficiency in the Kir channels predispose to fiber depolarization. One pharmacological strategy is based on blocking the Igp without affecting normal channel gating. It remains safe and effective the proposal of targeting the KATP, Kir channels or BK channels by drugs capable to specifically open at nanomolar concentrations the skeletal muscle subtypes with less side effects.